KESUBURAN PERAIRAN WADUK NAGEDANG DITINJAU DARI KOSENTRASI KLOROFIL-a FITOPLANKTON DESA GIRI SAKO KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Adnan Kasry; Eni Sumiarsih; Heriyanto ' (Berkala Perikanan Terubuk, 2009)
This research was conducted from Mei to June 2009 in the NagedangLakes Giri Sako Villages Logas Tanah Darat Sub-District Kuantan SingingiDistrict, Riau Province. The objective of this research was to predict waterproductivity as water fertilizing level from phytoplankton chlorophyll – α. Surveymethods were used for analysis this research were carried out by combining thephysic and chemical water parameters and also biological parameter(phytoplankton organism) observations.The predict results of this research that taken from 4 stations. It has beenfound average of chlorophyll- α as secchi depth were 37,783 – 43,766 (μg/l); 3class of phytoplankton such as Cyanophyta (15 species), Chlorophyta (11species), and Bacillariophyta (7 species) with average of phytoplanktonpopulation value were 29.873 – 48.237 ind/l; average of physical waterparameters that consist of depth : 235 – 792,3 m, thermo : 28,8 – 29 oC, secchi :74 – 80,3 cm, turbidy : 18,47 – 19,38 NTU, pH : 5,16 – 5,43: Oxygen : 5,26 –5,86 mg/l: carbon dioxide : 5,86 – 8,46 mg/l: Nitrate : 0,0606 – 0,0776 mg/l andphosphate : 0,0237 – 0,0253 mg/l. That value was mean that chlorophyll – α ofphytoplankton in Nagedang Lakes were very productive caused chlorophyllconcentration more than 20 μg/l and based on average of phytoplanktonpopulation shown that Nagedang Lakes were eutrophic (very fertilize) withpopulation more than 104 ind/l. Phytoplankton population had positive correlationwith chlorophyll concentration. The physical and chemical water parameter stillgood for aquatic organism such as phytoplankton and fishes.